Geography of the world economy / by Paul Knox, John Agnew [and] Linda McCarthy - Knox, Paul.; Agnew, John.; McCarthy, Linda (London, 2008)
The Geography of the World Economy provides an in-depth and stimulating introduction to the 'globalization' of the world economy. The book offers a consideration of local, regional, national and global economic development over the long historical term. The theory and practice of economic and political geography provide a basis for understanding the interactions within and among the developed and developing countries of the world.
Keywords: World economy